Relación Entre Los Niveles De Cortisol Y La Utilización Aromaterapia Con Base En Aceite Esencial De Lavanda, En La Fundación Mujer Linda Cats En La Ciudad De Bogotá (2022)
Behavior problems involving stress may have multiple consequences for both animals and the human-animal bond. For such reasons, It is necessary to have adequate indicators to scientifically assess the impact of the stress in the domestic species with which we live, as well as to assess their evolution during the application of treatment protocols. (Fletcher, 1995)